The association between travel time to health facilities and childhood vaccine coverage in rural Ethiopia. A community based cross sectional study - Okwaraji Yemisrach B; Mulholland Kim; Schellenberg JoannaRMArmstrong; Andarge Gashaw; Admassu Mengesha; Edmond Karen M (BMC, 2012)
Abstract Background Few studies have examined associations between access to health care and childhood vaccine coverage in remote communities that lack motorised transport. This study assessed whether travel time to health facilities was associated with childhood vaccine coverage in a remote area of Ethiopia. Methods This was a cross-sectional study using data from 775 children aged 12-59 months who participated in a household survey between January -July 2010 in Dabat district, north-western Ethiopia. 208 households were randomly selected from each kebele. All children in a household were eligible for inclusion if they were aged between 12-59 months at the time of data collection. Travel time to vaccine providers was collected using a geographical information system (GIS). The primary outcome was the percentage of children in the study population who were vaccinated with the third infant Pentavalent vaccine ([Diphtheria, Tetanus,-Pertussis Hepatitis B, Haemophilus influenza type b] Penta3) in the five years before the survey. We also assessed effects on BCG, Penta1, Penta2 and Measles vaccines. Analysis was conducted using Poisson regression models with robust standard error estimation and the Wald test. Results Missing vaccination data ranged from 4.6% (36/775) for BCG to 16.4% (127/775) for Penta3 vaccine. In children with complete vaccination records, BCG vaccine had the highest coverage (97.3% [719/739]), Penta3 coverage was (92.9% [602/648]) and Measles vaccine had the lowest coverage (81.7% [564/690]). Children living ≥60mins from a health post were significantly less likely (adjRR = 0.85 [0.79-0.92] p value < =0.001) to receive Penta3 vaccine compared to children living <30mins from a health post. This effect was not modified by household wealth (p value = 0.240). Travel time also had a highly significant association with BCG (adjRR = 0.95 [0.93-0.98] p value =0.002) and Measles (adjRR = 0.88 [0.79-0.97] p value =0.027) vaccine coverage. Conclusions Travel time to vaccine providers in health posts appeared to be a barrier to the delivery of infant vaccines in this remote Ethiopian community. New vaccine delivery strategies are needed for the hardest to reach children in the African region.